PENGARUH MODEL PEMBELAJARAN INQUIRY BASED LEARNING (IBL) DAN KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR SISWA KELAS X PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 6 PADANG - Raudhatul Jannah; Jimi Ronald; Mona Amelia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of the Inquiry Based Learning (IBL) model and emotional intelligence on the learning outcomes of grade X students in the Economics subject at SMA Negeri 6 Padang. The type of research used was quantitative with a quasi-experimental design. The research sample consisted of 60 students divided into two groups: 30 students in the experimental class taught using the IBL model and 30 students in the control class taught using the Direct Instruction model. The research instruments included an emotional intelligence questionnaire and a learning achievement test, which were then analyzed through validity tests, reliability tests, difficulty and discrimination index, normality and homogeneity tests, as well as two-way ANOVA using SPSS version 25. The findings of this study indicate that: (1) students taught with the IBL model achieved higher learning outcomes compared to those taught with Direct Instruction (tcount 8.706 > ttable 1.667); (2) students with high emotional intelligence taught with IBL obtained better results compared to Direct Instruction (tcount 7.905 > ttable 1.697); (3) students with low emotional intelligence also achieved higher results through IBL compared to Direct Instruction (tcount 4.215 > ttable 1.697); and (4) there was a significant interaction between the learning model and emotional intelligence on students’ learning outcomes (sig. 0.053 < α = 0.05). Thus, it can be concluded that the IBL model is more effective than Direct Instruction in improving students’ Economics learning outcomes, both for those with high and low emotional intelligence, and that the interaction of these variables significantly influences students’ academic achievement.